SYNTHESIS AND ANTIOXIDANT ACTIVITY OF THE 2-METHYL BENZIMIDAZOLE - Saini, Sarika; Dhiman, Neerupma; Mittal, Aman; Kumar, Gaurav (Journal of Drug Delivery and Therapeutics, 2016)
2-methyl benzimidazole is a heterocyclic organic compound having an important pharmacophoric group which is used in medicinal industry. o- Phenyldiamine was treated with acid in the presence of polyphosphoric acid and other solvents. The presence of specific group was determined by FTIR spectroscopy. The obtaining compound was screened by the antioxidant activity by using the DPPH method. Key words- 2- methyl benzimidazole, o- phenyldiamine, antioxidant activity, DPPH method.